Managerial perceptions of stakeholder salience in mining. Issue 4 (November 2016) - Viveros, Hector
Abstract: The purpose of this paper is to provide an understanding of stakeholder salience by exploring managerial perceptions of salience attributes in the mining industry in Chile. The study takes a qualitative approach to analyse semi-structured interviews using thematic analysis in relation to managers' perceptions. While managers have different views regarding salience attributes, legitimacy is unanimously considered as the most relevant attribute because it provides credibility, transparency and improving chances for networking. The findings also suggest that managers perceive communities, government and unions as the most salient stakeholders. However, views differ regarding NGOs and media, particularly regarding their legitimacy.